Stable isotopes of clay minerals from autoclave tests of oil sands : implications for clay formation during steaming of Alberta Clearwater oil sands - He, Shaoneng (2019)
In an effort to evaluate mineral-water isotopic exchange during cyclic steam stimulation (CSS), solutions and <2 μm berthierine-dominated solids from the Clearwater Formation oil sands of Alberta, Canada were analyzed for stable isotope compositions before and after reaction in autoclaves for 1008 hours at 250°C. There was no significant change in solution δ18O and δ2H, which is consisten with the high water/mineral ratio used in the experiments. The solids showed a marked decrease in both δ18O and δ2H following the experiments. Pre-run solids have δ18O of +9.5 to +12.9 ‰ and δ2H of −114 to −113 ‰, whereas post-run solids have δ18O of −4.7 to +2.1 ‰ and δ2H of −147 to −128 ‰. Neither oxygen- nor hydrogen-isotope equilibrium was established between the solids and the solutions. Calculation suggests that oxygen-isotope exchange (44-58%) was greater between the solids and solutions than was the case for hydrogen isotopes (23 to 50 %). We propose that this behaviour resulted from partial inheritance of the pre-run berthierine structure during formation of the post-run smectite, chlorite-smectite and chlorite. This process confounds the use of clay mineral stable isotope compositions as a temperature indicator of in situ steam/steam condensate interaction with oil-sands reservoirs. The results also suggest an additional mechanism by which new clay minerals can be formed during CSS-related, artificial diagenesis.